On some subclasses of interval catch digraphs - Sanchita Paul; Shamik Ghosh (Electronic Journal of Graph Theory and Applications (EJGTA), 2022)
A digraph G = (V, E) is an interval catch digraph if for each vertex v ∈ V, one can associate an interval on real line and a point within it (say (Iv, pv)) in such a way that uv ∈ E if and only if pv ∈ Iu. It was introduced by Maehara in 1984. It has many applications in real world situations like networking and telecommunication. In his introducing paper Maehara proposed a conjecture for the characterization of central interval catch digraph (where pv is the mid-point Iv for each v ∈ V) in terms of forbidden subdigraphs. In this paper, we disprove the conjecture by showing counter examples. Also we characterize this digraph by defining a suitable mapping from the vertex set to the real line. We study oriented interval catch digraphs and characterize an interval catch digraph when it is a tournament. Finally, we characterize a proper interval catch digraph and establish relationships between these digraph classes.